PLOT OF PERSONAL AND PROFESSIONAL CONNECTIONS FROM THE TEACHER'S VOICE - María Luisa García Martel; Ilda Avelina Mieres (Universidad Nacional del Nordeste, 2020)
This article is based on an inquiry about the curriculum vitae of a teacher and the analysis of it from the perspective related to the notion of curriculum as a space for disciplinary training. It made sense in this work the idea of significance, understood as the underlying principle of selection that explains the choices, attitudes, decisions and adhesions that the individual expresses and performs, in this particular case in relation to professional life. The qualitative approach was the methodological pillar of this work, since the aim was to understand a particular situation, contextualized in a certain historical time. Consequently, the perspective of the actors involved was revalued. In principle, the conclusions revolve around the possibility of describing the professional path of a teacher, showing different activities of a person in a specific spatial and temporal order. There are periods or stages at different levels and functions and there are also periods of acceleration and condensation of activities that suggest labor intensification. Likewise, there are temporary segments in which the trail is ruled, slow, serene, due to particular circumstances of personal life. It is worth stressing the importance exerted by the political and social pressures in times of occupying hierarchical positions, being the triggers of resignations in the professional performance. The question of significance put on the center stage the close relationship between the personal sphere and the professional sphere.